Does higher tax morale imply higher optimal labor income tax rate? - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
We analyze the impact of tax morale on the optimal progressive labor income taxation. Only universal basic income is financed from a linear tax and the financing of public goods is neglected. Each individual supplies labor and (un)declares earning, depending on his labor disutility and tax morale. Limiting the utilitarianism to the poorer parts of the population (defined by the inclusion share), the optimal tax rate is an increasing function of the tax morale and a decreasing function of the inclusion share, provide that the average wage of the included is higher than 0.54 times the average wage.
Keywords: H21; H26; H41; D58; 330; tax morale; progressive income tax; undeclared earning; labor supply; income redistribution; Steuermoral; Wirkungsanalyse; Einkommensteuer; Optimale Besteuerung; Steuerprogression; Arbeitsangebot